Pengaruh Waktu Reaksi Transesterifikasi terhadap Mutu Biopelumas dari Red Palm Stearin - Tambunan, Andi Supri Tambunan; Fatmayati, Fatmayati; Sihotang, Antonius Jumadi (ABEC Indonesia, 2023)
Currently, motor lubricants that are widely consumed are lubricants produced from the processing petroleum. The avaibility of petroleum as raw material for lubricants was decreasing. Therefore we need an alternative material can be further processed into alternative lubricants. This can be done by making biolubricant from processing vegetable oil derivatives. The purpose of this study was to determine the process of makin biolubricant from red palm stearin, to determine the effect of reaction time in the second stage of the transesterification reaction on the quality of biolubricant from red palm stearin and to produce bio lubricant with characteristics according to SNI No. 06-7069.5-2005. Research on the manufacture of this bio lubricant made from red palm stearin used a transesterification process. The fixed variable in the study were temperature 150°C, stirring in 400 rpm, mole ratio 1 : 3.9. and 1% sodium methoxide catalyst. And the variables of this study were the transesterifications time for making triesters TMP, namely 120,150,180,210, and 240. The analysis carried out was analysis of yield, density, viscosity, viscosity index, and corrosion rate. The results of this study showed that the length of time for step 2 transesterification had an effect on viscosity, viscosity index, corossoin rate, and yield. The optimal transesterification time of step 2 is 210 minutes to produce a biolubricant with a kinematic viscosity of 14.7991 cst at 40°C, 6,0991 AT 100°C, a viscosity index of 443 and a corrosion rate of 1.083 mpy.